Cardiovascular Imaging in Stress Cardiomyopathy (Takotsubo Syndrome) - Zghyer, Fawzi; Botheju, W. Savindu Pasan; Kiss, Joshua E.; Michos, Erin D.; Corretti, Mary C.; Mukherjee, Monica; Hays, Allison G. (Frontiers in Cardiovascular Medicine, 2022)
Stress cardiomyopathy (Takotsubo syndrome) is a reversible syndrome stemming from myocardial injury leading to systolic and/or diastolic dysfunction and is usually noted in the setting of a stressful event, be it an emotional or physical trigger. While the exact pathophysiology behind stress cardiomyopathy is yet unknown, there is ample evidence suggesting that neurocardiogenic mechanisms may play an important role. Although historically stress cardiomyopathy was generally thought to be a relatively benign condition, there is growing recognition of the cardiovascular complications associated with it despite its reversibility. Our review aims to shed light onto key cardiovascular imaging modalities used to diagnose stress cardiomyopathy while highlighting the role that imaging plays in assessing disease severity, identifying complications, dictating treatment approaches and in short-term and long-term prognosis.